2009
DOI: 10.5539/ijbm.v4n2p97
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Management as a Sustainable Performance Booster for the Accommodation Enterprises: Evidence from North Cyprus Tourism Sector

Abstract: The main purpose of the article is to assess the supply chain practices of the hotels and to reveal effects of such practices on the hotels' performance. Supply chain applications comprise relationships of hotels with their suppliers, tourism intermediaries and customers. In order to obtain sustainable performance development, hotel management should understand the key factors that have higher contribution. This study aims to investigate these factors as sources of superior performance in the competitive marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The fact that most of these studies were conducted in developed countries such Canada, Finland makes us to consider origin of this study, a developing country, might be one of the explanations behind this finding. Öztüren and Sevil (2009) studied collaborative relationships of hotels in North Cyprus which has a similar environment to Turkey. Accordingly, they found that hotels tend to have collaborative relationships with their customers, but not with their suppliers.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that most of these studies were conducted in developed countries such Canada, Finland makes us to consider origin of this study, a developing country, might be one of the explanations behind this finding. Öztüren and Sevil (2009) studied collaborative relationships of hotels in North Cyprus which has a similar environment to Turkey. Accordingly, they found that hotels tend to have collaborative relationships with their customers, but not with their suppliers.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the efficiency of the supply chain is strictly connected with the support provided to suppliers that is the result of long-term business relations and a stable customer market. Cooperation within a particular tourism-oriented supply chain is mainly focused on integrating the available resources and increasing the likelihood of the successful operation of individual suppliers [9]. Relations occurring within the scope of a tourism-specific supply chain can be characterized by taking advantage of the following criteria: Approach to a tourist as a member of the supply chain (direct, indirect) [10] Business goals resulting from relations between entities operating on the tourism-oriented market are directed towards the increase of generated income, cost reduction, maintaining relations with clients, increasing competitiveness, boosting efficiency, and ensuring satisfactory human resource management.…”
Section: Literature Reviewmentioning
confidence: 99%